High-Performing Self-Powered Photosensing and Reconfigurable Pyro-photoelectric Memory with Ferroelectric Hafnium Oxide - Kumar, Mohit; Seo, Hyungtak (Advanced Materials, 2022)
With highly diverse multifunctional properties, hafnium oxide (HfO2) has attracted considerable attention not only because of its potential to address fundamental questions about material behaviors, but also its potential for applied perspectives like ferroelectric memory, transistors, and pyroelectric sensors. However, effective harvesting of the pyro-photoelectric effect of HfO2 to develop high-performing self-biased photosensors and electric writable and optical readable memory has yet to be developed. Here, a proof-of-concept HfO2-based self-powered and ultrafast (response time ≈ 60 µs) infrared pyroelectric sensor with a responsivity of up to 68 µA W−1 is developed. In particular, temporal infrared light illumination induced surface heating and, in turn, change in spontaneous polarization are attributed to robust pyro-photocurrent generation. Further, controllable suspension and reestablishment of the self-biased pyro-photocurrent response with a short electric pulse are demonstrated, which offers a conceptually new kind of photoreadable memory. Potentially, the novel approach opens a new avenue for designing on-demand pyro-phototronic response over a desired area and offers the opportunity to utilize it for various applications, including memory storage, neuromorphic vision sensors, classification, and emergency alert systems.
Keywords: Ferroelectric; Photoelectrics; Photosensing; Powered devices; Pyro-photoelectric; Pyroelectric sensors; Reconfigurable; Self-biased; Self-powered; Self-powered device